A Prescription for Global Education in Health and Human Services. Issue 3 (14th August 2013) - Daly, Donna M.; Baker, Suzanne; Williams, Stephen J.
<x xml:space="preserve">Abstract</x> Study abroad might be associated primarily with humanities or business majors, but San Diego State University has mandated an international experience for all its health and human services students. Here's why.